Comparison of different concentrations atropine in controlling children and adolescent myopia: an umbrella review of systematic reviews and meta-analyses - Chen, Baizhou; Ni, Yao; Chen, Jinghan; Xing, Shuwen; Zhang, Zhaotian (Frontiers in Ophthalmology, 2024)
PurposeTo evaluate the myopia control effect of different concentrations atropine in children and adolescent.MethodsMeta-analyses and systematic reviews available in the Pubmed, Embase, and Cochrane Library databases from the databases’ inception to August 2023 were searched to evaluate the efficacy and tolerability of different concentrations’ atropine in controlling myopia progression. Overall effects were performed using random-effects model. AMSTAR 2 tool was used to assess the quality of included studies. Prespecified outcomes were weight mean difference (WMD) with 95% credible interval (95% CI) of annual spherical equivalent refraction (SER) changes and annual axial length (AL) changes.Results19 systematic reviews/meta-analyses of different atropine concentrations were included in the analysis. 14 studies reported SER changes, and 17 reported AL changes. In terms of the studies’ overall methodological quality level (measured using AMSTAR 2), 1 study was rated high, 7 moderate, 7 low, and 4 critically low. The 0.01% atropine was found to have statistically significance (annual SER change WMD 0.27 [95% CI 0.21 - 0.34] D/year; annual AL change WMD -0.09 [95% CI -0.1 to -0.07]) mm/year), 0.05% atropine was preferred considering efficacy and tolerability (annual SER change WMD 0.54 [95% CI 0.49 - 0.58] D/year; annual AL change WMD -0.21 [95% CI -0.12 to -0.02]) mm/year).ConclusionsDifferent atropine concentrations alleviated children and adolescent myopia progression. However, higher-quality evidence and further investigation are needed to clarify the dose–response relationship, and practical guidelines must be developed to determine myopia control efficacy.